The Effect Of Kasgotchar And Npk Application On The Production Of White Mustard (Brassica pekinensis L.) Variety Masita 140 - Irawati Sriningrum; Syarifa Mayly; Lisdayani Lisdayani; Dini Mufriah (Protech Biosystems Journal, 2025)
The low production of white mustard greens in Indonesia is due to the lack of organic matter content in the soil needed by plants. The addition of optimal organic matter, one of which is the utilization of bioconversion technology of organic waste of black soldier fly larvae. The purpose of this study was to determine the effect of kasgotchar and NPK applications on the production of white mustard greens (Brassica pekinensis L.) variety Masita140. This study used a Factorial Randomized Block Design with 2 factors: Factor l, namely the provision of Biochar kasgot fertilizer (K) with 3 levels, namely: K0 = Control (0 kg / plot), K1 = 10 tons / ha (1 kg / plot), K2 = 20 tons / ha (2 kg / plot). Factor 2, namely the provision of NPK fertilizer 16: 16: 16 (P) with 4 levels, namely: N0 = Control (0 kg / plot), N1 = 100 kg / ha (0.01 kg / plot), N2 = 200 kg / ha (0.02 kg / plot), N3 = 300 kg / ha (0.03 kg / plot). The parameters observed in this study include Fresh Weight per crop, fresh weight per plot and production per hectare (tons). The results of the study showed that the use of kasgotchar and NPK fertilizers did not differ significantly on Fresh Weight per crop, fresh weight per plot and fresh weight per hectare. The best treatment was the K2N3 treatment (kasgotchar with a dose of 2 tons / ha, and NPK with a dose of 300 kg / ha